Research on Issues and Development Strategies of Home-School-Community Integrated Physical Education Under the Educational Alliance Framework in China - Jingjing Zhou (Research and Advances in Education, 2024)
Against the backdrop of China’s current educational reform and the rapid development of its sports sector, the integrated development of “home-school-community” physical education within the framework of the “educational alliance” offers a new pathway for enhancing the quality of sports education and improving national physical fitness. Using literature review and logical analysis as research methods, this study identifies the existing issues in the integrated development of “home-school-community” physical education, including imbalanced resource allocation, incomplete collaboration mechanisms, insufficient awareness of physical education. Development strategies are proposed, such as Integrating Multi-Party Sports Resources, Establishing a Robust Collaborative Mechanism, and Enhancing Awareness of Home-School-Community Integrated Development in Physical Education.